2010
DOI: 10.17305/bjbms.2010.2743
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase and Oxidative Stress Activity in Primary Open-Angle Glaucoma Aqueous Humour

Abstract: Lactate dehydrogenase (LDH) and lactate are some of the hypoxy biochemical parameters. Extracellular activity of this enzyme increases under the condition of oxidative stress, since the cell integrity can be disrupted during the lipid peroxidation process. Subsequently that leads to the increase level of the lactic acid and lactic acid salts. The objective of this investigation is establishing the level of LDH, LDH1 (HBDH) and the lactate concentration in aqueous humour in patients with primary open-angle glau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 32 publications
4
35
1
3
Order By: Relevance
“…This event can be quantified in tissue culture settings by measuring the release of the intracellular enzyme lactate dehydrogenase (LDH). To confirm results of our histological study and detect cell damage and or death, we analyzed the level of this enzyme in the brain; Our results showed that after intoxication at short and long period by Al; the LDH levels increase significantly compared to control, indicating damaged membranes and cell necrosis [61][62]. Consistent with other results in this study, the Al+AER treated group induced decrease in LDH activity.…”
Section: Discussionsupporting
confidence: 86%
“…This event can be quantified in tissue culture settings by measuring the release of the intracellular enzyme lactate dehydrogenase (LDH). To confirm results of our histological study and detect cell damage and or death, we analyzed the level of this enzyme in the brain; Our results showed that after intoxication at short and long period by Al; the LDH levels increase significantly compared to control, indicating damaged membranes and cell necrosis [61][62]. Consistent with other results in this study, the Al+AER treated group induced decrease in LDH activity.…”
Section: Discussionsupporting
confidence: 86%
“…The isoenzymes of LDH include LDH1, LDH2, LDH3, LDH4, and LDH5, and the level of LDH1 in the myocardium is higher than the level of the other isoenzymes [ 25 ]. Finally, HBDH uses α -HBDH as a substrate, which reflects the sum of LDH1 and LDH2 activities [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, imidacloprid-induced oxidative stress in H. armigera larvae in a dose-and time-dependent manner as evidenced by increased levels of H 2 O 2 content, and lipid peroxidation in insecticide-fed larvae. Increased extracellular activity of LDH enzyme under oxidative stress condition was consequently observed due to the loss of cell integrity during the lipid peroxidation process (Jovanović et al 2010). In general, antioxidant enzymes are the potent scavengers of ROS, but the inhibition observed in the activities of CAT and SOD enzymes may be because of direct interaction of the insecticide with the enzymes, thereby resulting in increased levels of H 2 O 2 content and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%